2021
DOI: 10.3390/app11157094
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Physical Properties of Crude Palm Oil with Higher Oleic Content

Abstract: Interspecific hybridization of oil palms (E. guineensis × E. oleifera) was initially exploited to provide disease resistance and, consequently, increased oleic acid content. Besides the growing importance of this cultivar to the market, there is little information about this oil’s properties. In this context, this study aimed to determine a comprehensive physicochemical and thermal characterization of hybrid palm oil (HOPO) compared with the better-known African palm oil (APO). Differences in the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
2
11
0
2
Order By: Relevance
“…The fatty acid composition in both oils was in agreement with the typical ranges provided in the literature. Studies have shown that the fatty acids composition of HOPO were oleic (59.0–54.1%), palmitic (29.7%–17.5%), and linoleic acids (15.5%–7.35%) (de Almeida et al, 2021; Hollander, 2013; Ramli et al, 2008; Ramli et al, 2009), while those of HSO was reported between the ranges of 80.52%–75.2%, 16.2%–9.57%, and 7.43%–6.8%, respectively (Özdemir et al, 2014; Özyurt et al, 2020). Differences in fatty acid composition between the current study and the literature may be due to different growing and processing conditions (Ricaurte et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid composition in both oils was in agreement with the typical ranges provided in the literature. Studies have shown that the fatty acids composition of HOPO were oleic (59.0–54.1%), palmitic (29.7%–17.5%), and linoleic acids (15.5%–7.35%) (de Almeida et al, 2021; Hollander, 2013; Ramli et al, 2008; Ramli et al, 2009), while those of HSO was reported between the ranges of 80.52%–75.2%, 16.2%–9.57%, and 7.43%–6.8%, respectively (Özdemir et al, 2014; Özyurt et al, 2020). Differences in fatty acid composition between the current study and the literature may be due to different growing and processing conditions (Ricaurte et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Palm oil and its components are increasingly used in foods such as cooking oils, margarines, shortenings, and confectionery products. It contains 50% saturated fatty acids, 40% monounsaturated fatty acids, and 10% polyunsaturated fatty acids [193]. Oil palm phenolics have been shown to have anti-carcinogenic activities.…”
Section: Palm Oil Phenolics and Palm Juicementioning
confidence: 99%
“…Asimismo, el ácido linoleico, en las mismas muestras, resultó en un contenido promedio de 11,16 % m/m, con un mínimo de 10,93 % m/m y un máximo de 11,48 % m/m; mientras que el ácido palmítico fue determinado en una concentración porcentual másica promedio de 29,80 % m/m, con 28,92 % m/m como contenido mínimo y 30,40 % m/m como contenido máximo. Resultados similares pudieron ser encontrados en otros estudios desarrollados por distintos autores (Astorkia et al, 2019;de Almeida et al, 2021;Morcillo et al, 2021).…”
Section: Perfil De áCidos Grasos Y Cambios Composicionales De Las Esp...unclassified